2009
DOI: 10.1104/pp.109.146126
|View full text |Cite
|
Sign up to set email alerts
|

Grain Unloading of Arsenic Species in Rice  

Abstract: Rice (Oryza sativa) is the staple food for over half the world's population yet may represent a significant dietary source of inorganic arsenic (As), a nonthreshold, class 1 human carcinogen. Rice grain As is dominated by the inorganic species, and the organic species dimethylarsinic acid (DMA). To investigate how As species are unloaded into grain rice, panicles were excised during grain filling and hydroponically pulsed with arsenite, arsenate, glutathione-complexed As, or DMA. Total As concentrations in fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
224
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(239 citation statements)
references
References 39 publications
14
224
0
1
Order By: Relevance
“…These results indicate that methylated As, particularly the dimethyl species, are more mobile than inorganic As in the phloem. Consistent with this finding, Carey et al (2010) showed that DMA(V) was transported to rice grain much more efficiently than inorganic As. Uptake of undissociated MMA(V) and DMA(V) by rice roots is partly mediated by the aquaporin NIP2,1 (Li et al, 2009), but membrane transporters responsible for loading and unloading of methylated As species in phloem remain unknown.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These results indicate that methylated As, particularly the dimethyl species, are more mobile than inorganic As in the phloem. Consistent with this finding, Carey et al (2010) showed that DMA(V) was transported to rice grain much more efficiently than inorganic As. Uptake of undissociated MMA(V) and DMA(V) by rice roots is partly mediated by the aquaporin NIP2,1 (Li et al, 2009), but membrane transporters responsible for loading and unloading of methylated As species in phloem remain unknown.…”
Section: Discussionsupporting
confidence: 78%
“…It has been shown that phloem transport contributes substantially to As accumulation in rice grain (Carey et al, 2010). However, little is known about how As is transported in phloem ).…”
mentioning
confidence: 99%
“…In the less mature root region and in lateral root junctions, As(III) was poorly correlated with S within the (pre)vascular cylinder (Figures 1 and 3) and this likely indicates the presence of more free As(III) i there. Free As(III) i is both xylem and phloem mobile [38,39]. Free As(III) i that is transported to the stele in lateral root junctions and apical regions may access the (meta)xylem and ultimately be transported to shoots, including grain.…”
Section: Discussionmentioning
confidence: 99%
“…The translocation efficiency of DMA to the rice grain is over an order of magnitude greater than inorganic species in As-fed excised panicles. It is because that DMA is more mobile than As(III) in both the phloem and the xylem [100]. Organic As (DMA and MMA) was mainly distributed in reproductive tissues rather than vegetative tissues.…”
Section: Benefits Of Microbial Arsenic Methylation and Volatilizationmentioning
confidence: 94%